History and civilization from an Islamic perspective - Akhmetova, Elmira (2017)
This paper studies the concepts of civilisational developments, man and religion in comparison between the Western and Islamic approaches with the aim of highlighting the necessity of Islamisation of the subjects of history and social sciences. It also elaborates the idea of Islamisation of Knowledge and its relevance in the light of the subject of history. As paper finds, if social development in the mainstream Western thought was explained by the theory of unilineal evolution, Muslim scholars believed in a cyclical process in civilisation. Yet, the fundamental difference between their descriptions of social progress is related to the position of man in that development.